Thrombin activatable fibrinolysis inhibitor as an indicator of the severity of acute pancreatitis - Radovanović-Dinić, Biljana; Tesic-Rajkovic, Snezana; Ignjatovic, Aleksandra; Grgov, Saša (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Thrombin Activatable Fibrinolysis Inhibitor (TAFI), in addition to suppressing fibrinolysis, can be involved as a natural anti-inflammatory molecule in the inflammatory process in acute pancreatitis (AP). The goal of this study was to discover the significance of early determination of the values of TAFI in the assessment of the severity of AP. Materials and Methods: The prospective study included 92 patients with AP. In accordance with the revised Atlanta classification, we divided all patients into 3 groups (I-mild AP, II- moderate AP and III-severe AP). All patients were further classified into group A (mild AP) and group B (moderate and severe AP) with the aim of separating the patients with complicated and potentially bad prognosis. Biochemical markers, inflammatory biomarkers, coagulation parameters and TAFI were analyzed in all patients. Results: The level of TAFI were significantly higher among the patients with the complicated form (group B) of AP (p=0.002). The analysis of the ROC curve in regard to the inflammatory biomarkers (fibronectin and CRP) has shown that TAFI possesses the best discriminatory ability for complicated forms of AP (AUC=0.724, p=0.013), with the sensitivity of 83.30% and the specificity of 56.00%. Conclusion: The level of TAFI in plasma is higher in patients with moderate or severe AP. Determining the level of TAFI as a single parameter has a greater significance in the early estimation of the severity of AP than inflammatory biomarkers that we have analyzed. Cite this article as: Radovanović-Dinić B, Tešić-Rajković S, Tešić-Rajković S, Grgovd S. Thrombin activatable fibrinolysis inhibitor as an indicator of the severity of acute pancreatitis. Turk J Gastroenterol 2018; 29: 488-93.